2016
DOI: 10.1371/journal.pone.0164952
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Staff Shortage after the 2011 Triple Disaster in Fukushima, Japan-An Earthquake, Tsunamis, and Nuclear Power Plant Accident: A Case of the Soso District

Abstract: IntroductionIn 2011, Fukushima was struck by a triple disaster: an earthquake, tsunamis, and a nuclear accident. In the aftermath, there was much fear among hospital staff members about radiation exposure and many staff members failed to report to work.ObjectivesOne objective is to measure this shortage in hospital staff and another is to compare the difference in recovery by hospital types and by categories of hospital staff.DesignThe monthly records of the number of staff members from May 2011 to September 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 11 publications
0
60
2
Order By: Relevance
“…As a result of disasters, lack of basic health care resources (including equipment, supplies, and manpower) is known to last for only weeks to months. 12 Therefore, if nonevacuation with sufficient resources is not guaranteed, evacuation could be a reasonable option. Here, the present study adds evidence on survival of evacuees after the Fukushima incident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of disasters, lack of basic health care resources (including equipment, supplies, and manpower) is known to last for only weeks to months. 12 Therefore, if nonevacuation with sufficient resources is not guaranteed, evacuation could be a reasonable option. Here, the present study adds evidence on survival of evacuees after the Fukushima incident.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a unique, independent study in Fukushima could provide new insights into the strategy to prevent the disaster-related death of vulnerable people, particularly in light of the increasing severity and frequency of disasters worldwide. 12,13 Empirical evidence from Tokiwakai Group hospitals might be helpful in revealing the characteristics of evacuation of dialysis patients under certain circumstances.…”
mentioning
confidence: 99%
“…Hospital staff can be and often are impacted personally by noninfectious disasters in their communities, such as hurricanes and earthquakes, with effects on their ability to come to work and care for patients. 20,21 In caring for patients with infectious diseases during epidemics, however, much of the risk to HCWs is a direct result of their actual work and not a general risk to their community; as such, training and institutional precautions need to be implemented to both protect staff and reduce absenteeism. 22,23 "Stuff": Supply Requirements for Pandemic Preparedness…”
Section: Intensive Care Unit Planning For Pandemicsmentioning
confidence: 99%
“…Those who chose not to work did so primarily because of family demands, fear for their family's safety, and societal disapproval (Kollie et al, 2017). In another study, only 48% of Japanese nurses reported to work 1 month after the Fukushima earthquake (Ochi et al, 2016). A study of over 3,400 hospital workers, including 573 nurses, at one institution in the United States found that 39% of the respondents were not willing to respond to requests to work in the instance of a radiological bomb (Balicer et al, 2011).…”
Section: Review Of the Literaturementioning
confidence: 99%